Proposed Marketing Strategy for Y Supermarket to Increase Sales of Organic Products - Silalahi, Ezron Martin Vivaldi; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2013)
Gap between people's attitudes and actions towards environmental sustainability was the problem faced by the Y Supermarket, where the organic products that sold are still less desirable by people in Bandung city. Based on internal and external analysis, there are some deficiencies owned by Y Supermarket in selling organic products. Y Supermarket in selling organic products do not know clearly who their target market. Based on a survey conducted, level of public awareness relatively low. Lack of awareness of some people can cause not all branches of the Y Supermarkets sell organic products, conditions display organic products that are less regularly, and Y Supermarket does not provide store sign about organic products in the supermarket area. Moreover, there are some things that can reduce the interest of consumers to buy organic products based on the situations at the supermarket, the price of organic products are expensive, not all organic products are sold have organic certification, and lack of information provided by service crew to consumer. Some alternative solutions that can be used as a marketing strategy for Y Supermarket to increase awareness and people's interest in organic products are has clear target market, offering organic products that have official certification, creating private label for organic products, provide organic product mix, providing organic products in every branch of Y Supermarket, provides short training for all staff fresh departments, made standard the organic product display in area supermarkets, and conducted promotion such as; social media, special event, in-store promotion, brochures, special discount, and create donation program for environment movement.Ã‚Â Keywords: Marketing Mix, Supermarket, Organic Product, Awareness